Prevalence and factors associated with polyneuropathy in Parkinson’s disease - Crespo-Burillo, José Antonio; Almarcegui-Lafita, Carmen; Dolz-Zaera, Isabel; Alarcia, Raquel; Roche, José Carlos; Ara, José Ramón; Capablo, José Luis (Basal ganglia, 2016)
Data on polyneuropathy rates in Parkinson’s disease vary between studies. Our purpose was to determine its prevalence and the factors associated with that entity. Presence of polyneuropathy was determined using the Utah Early Neuropathy Scale and a nerve conduction study in patients with Parkinson’s disease. We established 2 subgroups of patients with polyneuropathy by clinical relevance: patients scoring ≥5 on the Utah Early Neuropathy Scale, and patients scoring <5 but with a neurophysiological study compatible with polyneuropathy. Eighty-four subjects were included in the study. Prevalence of polyneuropathy was 30.9%; 21.4% of the patients scored ≥5 and 9.5% scored <5. According to the multivariate analysis, factors associated with polyneuropathy were older age at onset of Parkinson’s disease and more advanced stages of the disease according to the Hoehn and Yahr scale. Associated factors were older age and low levels of vitamin B12 for the subgroup scoring ≥5, but only age at disease onset for the subgroup with lower scores. Polyneuropathy may have a primary neurodegenerative origin in relationship with older age at onset of Parkinson’s disease and more advanced stages of the disease. Decreases in vitamin B12 levels may contribute to exacerbation of polyneuropathy in these patients.